Geoheritage and geotourism. A European perspective, by T.A. Hose (Ed.). The Heritage Matters Series, volume 19. Boydell Press, Woodbridge. - Migoń, Piotr (Geologos, 2018)
Review: Geoheritage and geotourism. A European perspective, by T.A. Hose (Ed.). The Heritage Matters Series, volume 19. Boydell Press, Woodbridge. 336 pages. Hardback: price £60.00, ISBN 978-1-78327-147-4.